Analysis of dietary patterns, intake, output performance, and blood lactate concentration according to athlete career : A study on elite Korean wrestlers - Lee, Y. S.; Lee, D. R.; Baik, H. J.; Cho, J. H.; Sung, J. Y. (International Journal of Applied Sports Sciences, 2021)
The aim of this study was to assess the eating habits of Korean wrestlers, and to explore the impact of differences in dietary intake on power output performance and blood lactate concentrations. Thirty adult wrestlers with more than seven years of experience each were included, grouped according to their competitive level (national, senior, and university team level). Participants recorded their dietary intake for seven days; nutritional analysis was performed using the CAN-Pro 4.0 software. After the nutritional survey, power output performance (Wingate test) was evaluated and blood parameters, including lactate concentration, were assessed. The wrestlers` dietary assessments revealed differences in carbohydrate, protein, and fat intake among the groups, as well as differences in the peak power, mean power, and change in peak power, obtained from the Wingate test. Finally, the senior group had a significantly higher and lower lactate concentration than the university group immediately post training and 30 minutes post training, respectively. Follow-up studies should reveal more accurate associations between nutritional intake, nutritional quality, and performance. Finally, considering a study concerning nutrition and weight loss based on the results from this study, including not only wrestlers but also combat sport athletes will benefit nutrition education as well as athletes` intake and performance.